2016
DOI: 10.1002/prot.25087
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the structure and catalytic activity of Legionella pneumophila VipF

Abstract: The pathogenic bacteria Legionella pneumophila is known to cause Legionnaires' Disease, a severe pneumonia that can be fatal to immunocompromised individuals and the elderly. Shohdy et al. identified the L. pneumophila vacuole sorting inhibitory protein VipF as a putative N-acetyltransferase based on sequence homology. We have characterized the basic structural and functional properties of VipF to confirm this original functional assignment. Sequence conservation analysis indicates two putative CoA-binding reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(78 reference statements)
1
4
0
Order By: Relevance
“…Among tested substrates, we observed that Lha0223 activity was highest against chloramphenicol, in line with the general activity reported for L. pneumophila VipF/Lpg0103 ( Fig. 1B ) ( 22 , 23 ). However, Lha0223 also demonstrated strong activity against poly-lysine substrate suggesting that it can be active against peptide or protein targets.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Among tested substrates, we observed that Lha0223 activity was highest against chloramphenicol, in line with the general activity reported for L. pneumophila VipF/Lpg0103 ( Fig. 1B ) ( 22 , 23 ). However, Lha0223 also demonstrated strong activity against poly-lysine substrate suggesting that it can be active against peptide or protein targets.…”
Section: Resultssupporting
confidence: 89%
“…A previous report suggested that both GNAT domains of Lpg0103 are active against chloramphenicol substrate. However, a more recent report established that VipF follows the general trend of tandem GNATs with only the C-terminal domain retaining the catalytic activity ( 22 , 23 ). Despite these insights into the biochemical activity of VipF, the significance of its acetyltransferase activity function for Legionella ’s invasion of the host cell has never been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…S2). Young and coworkers found that chloramphenicol is a putative substrate of VipF (Young et al, 2016). Indeed, VipF showed significant activity on chloramphenicol (Supplementary Fig.…”
Section: Chloramphenicol a Putative Substrate Is Placed In The Centra...mentioning
confidence: 92%
“…In addition, most of these effectors contain unknown protein sequence domains, except for Lpg1356, which contains multiple Sel1 repeats (Shohdy et al, 2005). Interestingly, VipF has dual GNAT-like domains that catalyze O-linked rather than N-linked acetylation of the putative substrate chloramphenicol (Young et al, 2016). Its enzymatic mechanism, however, has not been fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Lpg3000 is required for intracellular growth in Hartmannella vermiformis , and lpg0086 is required for intracellular growth in several host cells ( Shames et al., 2017 ; Park et al., 2020b ). In addition, most of these effectors contain no known protein sequence domains, except for lpg1356, which harbors multiple Sel1 repeats and VipF, which contains an acetyltransferase domain and might be involved in membrane trafficking ( Shohdy et al., 2005 ; Young et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%